BUILD THE POSITIVE WORK ENVIRONMENT WITH WORK ENGAGEMENT - Sari, Siti Melinda; Ranihusna, Desti (Management Analysis Journal, 2019)
The purpose of this study is to analyse the effect of organizational justice and authentic leadership on work engagement with organizational trust as a mediating variable. The sample in this study amounted to 154 nurses. The sampling technique uses probability sampling with proportionate random sampling. The data collection method uses a questionnaire that is measured by a Likert scale. The analytical method used is descriptive statistical test and SmartPLS software version 3.0. The results showed that organizational justice and authentic leadership had a positive and significant effect on organizational trust, and had an influence on nurses' work engagement. In addition, the results also show that organizational trust is able to mediate the influence of organizational justice and authentic leadership on work engagement. In other words, the role of organizational trust will further increase the level of work engagement of nurses. This research is expected to be an input for hospitals on the importance of the role of strategies to increase work engagement through organizational justice and the role of leaders.